Psychological factors in basketball talent identification: a systematic review and meta-analysis - Han, M.; Lorenzo-Calvo, J. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Introduction Identifying athletic talent involves assessing physical, motor, and psychological factors. Cognitive perceptual skills are crucial in basketball because they allow for quick decision-making and efficient movement [1]. Expert players use visual search strategies to predict outcomes, while novices struggle with effective gaze patterns. Although many studies have explored visual interventions with adult athletes, few studies have investigated the impact of visual perception, particularly in the selection of young athletes. This study conducted a systematic review and meta-analysis to identify psychological factors in basketball talent (1) to find out whether visual perception affects talent identification in youth players and (2) whether visual search behaviour training applies to youth players of all ages. Methods The search was carried out using the most relevant databases, such as Web of Science, PubMed, SPORTDiscus, and Scopus, according to the PRISMA (2020) guideline. Keywords such as `basketball`, `talent identification,selection`, `psychological`, `perceptual cognitive`, `decision making`, basketball, and `visual` were used for the search in English, following the PICOS question model. Meta-analyses were performed using Cochrane Collaborations Collaboration Review Manager 5.4.1, an open-source programme. A total of 33 articles were evaluated for overall methodological quality using critical review forms. Results The findings highlight the complexity of the interactions between psychological factors, training interventions, and motor skills for identification in basketball talent. Visual perception affects their response time, shooting accuracy, and movement time during the game. Players visual behaviour and their reactions to opponents are influenced by factors such as peripheral vision. Expert players performed better in terms of visual behaviour. The role of reaction time, gender, age, and peripheral perception in predicting the role of vision and visual attention in improving performance is also stressed, as is the importance of focusing on the direction of the pass to mitigate the effects of high frequency. Conclusion The results demonstrated the importance of these psychological and perceptual factors in maximising the performance and success of the court. It also revealed the complex relationship between basketball players visual behaviour and performance, which indicated the viability of visual and motor performance assessment for coaches and scouts looking for talent.